Core-shell-satellite SERS (Surface Enhanced Raman Scattering) composite substrate with copper-doped MOF (Metal Organic Framework) shell layer and preparation method thereof
By introducing copper-doped MOF shell and gold nanosphere structure into the SERS substrate, the synergistic effect of the electromagnetic field and chemical enhancement of the Au@Ag nanostructure is achieved, solving the shortcomings of the existing SERS substrate in the chemical enhancement mechanism and improving the The accuracy and sensitivity of the detection are achieved.
Patent Information
- Application Number
- CN202411416717.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-10
AI Technical Summary
The existing SERS substrates have poor performance in chemical enhancement mechanisms, making it difficult to achieve further improvement in Au@Ag nanostructures, and the demand for detection accuracy and sensitivity has not been met.
Using a core-shell-satellite SERS composite substrate with copper-doped MOF shell, gold and silver nanoparticles Au@Ag as the core, copper ions doped MOF material as the shell, and gold nanospheres are grown on the MOF surface to achieve Synergistic effects of electromagnetic fields and chemical enhancement.
Free carriers are introduced through doping technology, reducing the bandwidth of the bandage, promoting charge transfer, achieving enhanced chemical enhancement, and enhancing electromagnetic field enhancement through the electric field coupling between satellites and nuclei, achieving a coordinated improvement of SERS activity.
Smart Images

Figure CN119290844A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano material synthesis, and in particular to a core-shell-satellite SERS composite substrate with a copper-doped MOF shell layer and a preparation method thereof. Background Art
[0002] Surface enhanced Raman scattering (SERS) has become a promising spectral detection method due to its non-destructive and rapid acquisition of target molecular information. It is of great significance in the fields of food safety, biosensing, environmental assessment and trace analysis. Surface enhanced Raman is a technology that allows the target to be adsorbed on a rough metal surface with a nanostructure, so that the Raman signal of the molecule to be detected can be greatly enhanced. The SERS enhancement mechanisms widely recognized by researchers at present mainly include electromagnetic field enhancement (EM) based on the coupling of incident light and substrate to produce localized surface plasmon resonance, and chemical enhancement (CM) caused by charge transfer between substrate and molecule. Among them, the development and preparation of high-performance composite SERS substrates is the key to obtaining strong SERS activity. Metal organic frameworks (MOFs) can improve the selectivity and stability of precious metal nanostructures, but MOFs, a semiconductor-like material, have a wide band gap and poor conductivity, so the chemical enhancement effect is not obvious. At present, the improvement of the morphology and structure of SERS substrates is mainly based on the electromagnetic field enhancement mechanism, but with the growing demand for detection accuracy and sensitivity in application fields such as food safety, the chemical enhancement mechanism has attracted more and more attention from researchers. Summary of the invention
[0003] The technical problem to be solved by the present invention is how to further improve the SERS activity of Au@Ag nanostructure from two aspects of chemical enhancement mechanism and physical enhancement mechanism, so as to prepare a new SERS substrate with synergistic enhancement performance.
[0004] The present invention solves the above technical problems by the following technical means:
[0005] A core-shell-satellite SERS composite substrate with a copper-doped MOF shell layer, which has gold-silver nanoparticles Au@Ag as the core, a MOF material doped with copper ions as the shell, and gold nanospheres grown on the surface of the MOF material doped with copper ions as the satellites; wherein the gold-silver nanoparticles Au@Ag include gold nanoparticles and a silver layer wrapped on the gold nanoparticles; and the MOF material doped with copper ions is a ZIF-8 material doped with copper ions.
[0006] Beneficial effects: The prepared Au@Ag@(MOF+Cu)-AuNPs core-shell-satellite structure has electric field coupling between satellites and cores, achieving strong electromagnetic field enhancement. At the same time, the doping process can introduce more free carriers, reduce the bandgap width, promote charge transfer, and achieve strong chemical enhancement.
[0007] Preferably, in the ZIF-8 material doped with copper ions, the doping molar amount of copper is 5-15% of the molar amount of zinc ions, wherein the optimal doping molar amount is 10%.
[0008] Preferably, in the Au@Ag core, the molar ratio of gold in the gold nanoparticles to silver in the silver layer is 25:16.7; the molar ratio of gold in the gold nanoparticles forming the core to gold in the gold nanospheres forming the satellites is 16:1.
[0009] Preferably, the surface of the gold and silver nanoparticles is also modified with Raman probe molecules.
[0010] Preferably, the Raman probe molecule is 4-aminothiophenol.
[0011] The present invention also proposes a method for preparing the core-shell-satellite SERS composite substrate having a copper-doped MOF shell layer, comprising the following steps:
[0012] S1, preparing gold nanoparticles, and in situ coating the gold nanoparticles with a silver layer to obtain gold-silver nanoparticles;
[0013] S2, using Raman probe molecules to modify gold and silver nanoparticles to obtain modified gold and silver nanoparticles;
[0014] S3, modifying MOF materials doped with copper ions on the gold and silver nanoparticles modified by S2;
[0015] S4. Growing gold nanospheres on the surface of the material obtained in S3 to obtain the core-shell-satellite SERS composite substrate with a copper-doped MOF shell layer.
[0016] Preferably, in S1, a gold nanoparticle solution is prepared by heating and stirring with chloroauric acid aqueous solution and sodium citrate aqueous solution as raw materials; a silver nitrate aqueous solution is added to the gold nanoparticle solution under stirring, and then an ascorbic acid aqueous solution is added, and gold-silver nanoparticles are obtained after stirring; in S2, the following steps are specifically included: the gold-silver nanoparticles are dispersed in a polyvinyl pyrrolidone aqueous solution, mixed with a Raman probe molecule aqueous solution after stirring, and allowed to stand after dispersion to obtain modified gold-silver nanoparticles; in S3, the following steps are specifically included: the modified gold-silver nanoparticles are dispersed in methanol, a methanol solution containing zinc nitrate and copper nitrate is added under ice-water bath conditions, a 2-methylimidazole methanol solution is added after stirring, and allowed to stand after stirring; in S4, the following steps are specifically included: the product obtained in S3 is dispersed in water, added to the stirred chloroauric acid aqueous solution, a sodium borohydride aqueous solution is added, and stirred to obtain the core-shell-satellite SERS composite substrate with a copper-doped MOF shell layer.
[0017] Preferably, in S1, the molar ratio of chloroauric acid and silver nitrate is 25:16.7; the molar ratio of chloroauric acid used in S1 to the Raman probe molecule used in S2 is 1:8; the molar ratio of chloroauric acid used in S1 to zinc nitrate and 2-methylimidazole used in S3 is 0.32:1:3; the molar ratio of chloroauric acid used in S1 to chloroauric acid used in S4 is 16:1.
[0018] Preferably, in S1, the temperature of heating and stirring is 100°C and the time is 30 minutes.
[0019] Preferably, the amount ratio of chloroauric acid used in S1 to polyvinyl pyrrolidone used in S2 is 1 mmol:50 g; the molar ratio of chloroauric acid used in S1 to sodium borohydride used in S4 is 1:0.555.
[0020] The advantages of the present invention are:
[0021] Composite or doping is an economical and effective way to overcome poor conductivity. Therefore, alternative doping is chosen here to replace a small amount of zinc in the MOF (ZIF-8) structure with copper, which has a different but similar valence electron structure. Copper doping can introduce additional electronic states, significantly affect the electronic structure of the active site, reduce the gap between the highest occupied molecular orbital and the lowest unoccupied molecular orbital of the MOF layer, promote the charge separation and transfer rate between the entire assembly structure and different material layers, and achieve strong chemical enhancement. Then, gold nanosatellite beads are grown on the surface of the copper-doped MOF shell to construct a core-shell-satellite structure. The addition of gold nanosatellites can achieve electric field coupling between satellites and between cores and satellites, and has a strong electromagnetic field enhancement effect. The combination of the two can achieve synergistic enhancement of electromagnetic fields and chemistry, thereby providing a method for preparing a core-shell-satellite SERS composite substrate Au@Ag@(MOF+Cu)-AuNPs with a copper-doped MOF shell and the SERS synergistic enhancement effect that can be achieved.
[0022] Therefore, based on the electromagnetic field enhancement that can be achieved by Au@Ag dual noble metal nanoparticles, the present invention coats the surface of MOF materials and dopes the transition element copper in MOF to enhance the charge separation and transfer rate between molecules, thus exerting a good chemical enhancement effect. Gold nanospheres are grown on the surface of copper-doped MOF to further enhance the electromagnetic field coupling performance, so that the obtained SERS substrate has the synergistic enhancement performance of chemical and electromagnetic fields, providing support for subsequent further detection and application.
[0023] The preparation method of the invention has low energy consumption, simple operation and high efficiency, and the synthesized nanostructure has the advantages of being economical, effective and having good stability.
[0024] The SERS substrate prepared by the above preparation method and copper doping ratio has uniform structure and size, good comprehensive performance of chemical enhancement and electromagnetic enhancement, and can provide more accurate and sensitive detection results for subsequent SERS detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is the X-ray diffraction pattern of Au@Ag@MOF in Example 1 of the present invention;
[0026] Figure 2 This is a transmission electron microscope image of Au@Ag@(MOF+Cu 10%) at high magnification in Example 2 of the present invention;
[0027] Figure 3 This is a transmission electron microscope image of Au@Ag@(MOF+Cu 10%) at low magnification in Example 2 of the present invention;
[0028] Figure 4This is the X-ray photoelectron spectrum of Au@Ag@(MOF+Cu 10%) in Example 2 of the present invention;
[0029] Figure 5 The Raman spectra of Au@Ag@(MOF+Cu) with different copper doping ratios in Example 2 of the present invention are shown;
[0030] Figure 6 This is a comparison chart of the band gap values of Au@Ag@MOF in Example 1 of the present invention and Au@Ag@(MOF+Cu) in Example 2;
[0031] Figure 7 The electrochemical impedance diagrams of Au@Ag@MOF in Example 1 and Au@Ag@(MOF+Cu) in Example 2 of the present invention are shown;
[0032] Figure 8 The Raman spectra of Au@Ag@MOF in Example 1 and Au@Ag@MOF-AuNPs in Example 3 of the present invention are shown;
[0033] Fig. 9 This is a transmission electron microscopy image of Au@Ag@(MOF+Cu 10%)-AuNPs in Example 4 of the present invention;
[0034] Fig.10 These are the Raman spectra of Au@Ag@(MOF+Cu) in Example 2 of the present invention and Au@Ag@(MOF+Cu)-AuNPs in Example 4. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.
[0037] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0038] The chloroauric acid described below is all chloroauric acid tetrahydrate HAuCl 4 ·4H 2 O.
[0039] Example 1
[0040] The composite material Au@Ag@MOF in this embodiment includes gold-silver nanoparticles Au@Ag and MOF (ZIF-8) material. The silver layer is in situ wrapped outside the gold nanoparticles AuNPs and then coated with MOF material. The composite material is a core-shell structure, with the gold-silver nanoparticles as the core and the MOF layer as the shell.
[0041] The preparation method of the composite material in this embodiment comprises the following steps:
[0042] (1) Preparation of Au@Ag:
[0043] 100 mL (0.25 mM) of chloroauric acid aqueous solution was heated to boiling on a magnetic stirrer and stirred, 0.75 mL (1% wt) of sodium citrate aqueous solution was added, and the mixture was heated at 100°C and stirred for 30 min to obtain an AuNPs solution. 0.334 mL (50 mM) of silver nitrate aqueous solution was added to the cooled AuNPs solution under stirring with a magnetic stirrer, and then 0.334 mL (100 mM) of ascorbic acid aqueous solution was immediately added and stirred for 10 min to obtain an Au@Ag solution.
[0044] (2) Preparation of Au@Ag@MOF:
[0045] The obtained Au@Ag solution was centrifuged to remove the supernatant and then dispersed into 100mL (12.5g / L) polyvinyl pyrrolidone aqueous solution, and stirred at 200 rpm on a magnetic stirrer for 12h to obtain Au@Ag+PVP solution. The Au@Ag+PVP solution was mixed with 10mL (20mM) 4-aminothiophenol aqueous solution, ultrasonically dispersed and allowed to stand for 1h, centrifuged to remove the supernatant and dispersed into 100mL methanol to obtain the Au@Ag solution modified with 4-aminothiophenol. 16mL of the Au@Ag solution modified with 4-aminothiophenol was taken, stirred on a magnetic stirrer with ice water, 0.5mL (25mM) zinc nitrate methanol solution was added and stirred for 10min, 0.75mL (50mM) 2-methylimidazole methanol solution was added and stirred for 5min, then allowed to stand and incubate for 1h, centrifuged and washed three times, and then dispersed in 5mL methanol to obtain the Au@Ag@MOF methanol solution for storage.
[0046] like Figure 1 As shown, the synthesis of ZIF-8 crystal form was demonstrated.
[0047] Example 2
[0048] The composite material Au@Ag@(MOF+Cu) in this embodiment is based on Example 1, and copper ions are doped in the MOF material. It includes gold-silver nanoparticles Au@Ag, MOF (ZIF-8) material and copper ions. The silver layer is in situ wrapped outside the gold nanoparticles and then coated with the MOF material doped with copper ions.
[0049] The method for preparing the composite material in this embodiment comprises the following steps:
[0050] The Au@Ag solution synthesized in Example 1 was centrifuged to remove the supernatant and then dispersed into 100mL (12.5g / L) polyvinyl pyrrolidone aqueous solution, and stirred on a magnetic stirrer at a speed of 200 rpm for 12h to obtain an Au@Ag+PVP solution. The Au@Ag+PVP solution was mixed with 10mL (20mM) 4-aminothiophenol aqueous solution, ultrasonically dispersed and allowed to stand for 1h, centrifuged to remove the supernatant and then dispersed into 100mL methanol to obtain an Au@Ag solution modified with 4-aminothiophenol. 16mL of the Au@Ag solution modified with 4-aminothiophenol was taken and stirred on a magnetic stirrer with ice water. 0.5mL of a methanol solution containing zinc nitrate and copper nitrate was added and stirred for 10min, wherein in the methanol solution, the concentration of zinc nitrate was 25mM, and the molar number of copper nitrate was 5%, 10% and 15% of the molar number of zinc nitrate. 0.75 mL (50 mM) 2-methylimidazole methanol solution was added and stirred for 5 min, then incubated for 1 h. After centrifugation and washing three times, it was dispersed in 5 mL of methanol to obtain Au@Ag@(MOF+Cu) methanol solution for storage.
[0051] like Figure 2 and Figure 3 As shown, the synthesis of the morphology and the successful doping of Cu element are proved. It can be seen that the structure has good dispersion and size uniformity, where the average diameter of Au@Ag is about 40nm and the thickness of the ZIF-8+Cu shell is 2.7nm±0.95nm. Figure 4 This is the X-ray photoelectron spectrum of Au@Ag@(MOF+Cu). In the Cu spectrum, the two main peaks at 931.18 eV and 951.18 eV represent Cu 2p 3 / 2 and Cu 2p 1 / 2 , and no bulk copper oxidation peak was observed, which can further prove that a small amount of Cu successfully replaced Zn and coordinated with the zeolite imidazole molecules through the ion exchange strategy. Figure 5 The Raman spectra of Au@Ag@(MOF+Cu) with different copper doping ratios are shown in Figure 2. By comparing the Raman spectra of 0%, 5%, 10%, and 15% copper doping, it can be seen that Au@Ag@(MOF+Cu10%) (i.e., the molar number of copper doping is 10% of the molar number of zinc) has the best chemical enhancement effect (when 4-aminothiophenol is at 1578 cm -1 When the intensity of the completely symmetrical peak at 1135 cm is approximately equal, -1 The Raman intensity of the non-completely symmetric peak at ).
[0052] Figure 6The band gap values of Au@Ag@MOF and Au@Ag@(MOF+Cu10%) are compared. The overall band gap value before copper doping is 2.06eV, and the band gap value after copper doping is 1.95eV, which proves that doping can reduce the band gap value. Figure 7 The electrochemical impedance diagrams of Au@Ag@MOF and Au@Ag@(MOF+Cu10%) are shown below. The semicircle diameter in the high-frequency region is inversely proportional to the charge transfer rate of the material. It can be seen that the semicircle diameter of the Au@Ag@(MOF+Cu10%) material is smaller than that of the Au@Ag@MOF material, indicating that the presence of the Cu element can promote the charge transfer at the MOF interface and has a lower charge transfer impedance.
[0053] Example 3
[0054] The composite material Au@Ag@MOF-AuNPs in this embodiment is based on Example 1, and gold nanospheres are grown on the surface of the MOF material. The composite material is a core-shell-satellite structure, with gold and silver nanoparticles as the core, MOF material as the shell, and gold nanospheres grown on the surface of the MOF material as the satellite.
[0055] Preparation of Au@Ag@MOF-AuNPs:
[0056] The Au@Ag@MOF methanol solution obtained by dispersing in methanol after washing in Example 1 was centrifuged to remove the supernatant and then dispersed in 6 mL of water, added to 10 mL (0.025 mM) of chloroauric acid aqueous solution stirred by a magnetic stirrer, and 120 μL (18.5 mM) of sodium borohydride aqueous solution was added and stirred for 10 min to obtain an Au@Ag@MOF-AuNPs aqueous solution, thereby obtaining a core-shell-satellite SERS composite substrate with a MOF shell layer.
[0057] Figure 8 is the Raman spectra of Au@Ag@MOF and Au@Ag@MOF-AuNPs; Figure 8 It can be seen that growing gold nanosatellite spheres on the MOF surface of Au@Ag@MOF can generate more hot spots and enhance the SERS signal; wherein, Au@MOF is prepared according to the following process:
[0058] 100 mL (0.25 mM) of chloroauric acid aqueous solution was heated to boiling on a magnetic stirrer and stirred, 0.75 mL (1% wt) of sodium citrate aqueous solution was added, and the AuNPs solution was obtained after stirring at 100 ° C for 30 min. The obtained AuNPs solution was centrifuged to remove the supernatant and dispersed in 100 mL (12.5 g / L) of polyvinyl pyrrolidone aqueous solution, and stirred at 200 rpm on a magnetic stirrer for 12 h to obtain an AuNPs + PVP solution. The AuNPs + PVP solution was mixed with 10 mL (20 mM) of 4-aminothiophenol aqueous solution, ultrasonically dispersed and allowed to stand for 1 h, centrifuged to remove the supernatant and dispersed in 100 mL of methanol to obtain an AuNPs solution modified with 4-aminothiophenol. Take 16 mL of AuNPs solution modified with 4-aminobenzenethiol, stir it on a magnetic stirrer with ice water, add 0.5 mL (25 mM) zinc nitrate methanol solution and stir for 10 min, add 0.75 mL (50 mM) 2-methylimidazole methanol solution and stir for 5 min, then incubate for 1 h to synthesize AuNPs@MOF methanol solution. The synthesized AuNPs@MOF methanol solution is centrifuged and washed three times and then dispersed in 5 mL methanol for storage.
[0059] Example 4
[0060] The composite material in this embodiment, that is, the core-shell-satellite SERS composite substrate Au@Ag@(MOF+Cu)-AuNPs with a copper-doped MOF shell layer, is based on Example 2, with gold nanospheres grown on the surface of the MOF material. The composite material is a core-shell-satellite structure, with gold and silver nanoparticles as the core, MOF material doped with copper ions as the shell, and gold nanospheres grown on the surface of the MOF material as the satellite.
[0061] Preparation of Au@Ag@(MOF+Cu)-AuNPs:
[0062] The Au@Ag@(MOF+Cu) methanol solution obtained by washing and dispersing in methanol in Example 2 was centrifuged to remove the supernatant and then dispersed in 6 mL of water, added to 10 mL (0.025 mM) chloroauric acid aqueous solution stirred by a magnetic stirrer, and 120 μL (18.5 mM) sodium borohydride aqueous solution was added and stirred for 10 min to obtain an Au@Ag@(MOF+Cu)-AuNPs aqueous solution, and a core-shell-satellite SERS composite substrate with a copper-doped MOF shell layer was obtained. The morphology of the 10% copper-doped substrate is shown in FIG. Fig. 9 shown.
[0063] Fig.10 These are the Raman spectra of Au@Ag@(MOF+Cu) and Au@Ag@(MOF+Cu)-AuNPs (doped with 10% copper). It can be seen that the growth of gold nanospheres can further enhance the SERS signal.
[0064] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A core-shell-satellite SERS composite substrate with a copper-doped MOF shell layer, characterized in that: It uses gold and silver nanoparticles as the core, MOF material doped with copper ions as the shell, and gold nanospheres grown on the surface of the MOF material doped with copper ions as satellites; wherein the gold and silver nanoparticles include gold nanoparticles and a silver layer wrapped on the gold nanoparticles; the MOF material doped with copper ions is a ZIF-8 material doped with copper ions.
2. The core-shell-satellite SERS composite substrate with a copper-doped MOF shell layer according to claim 1, characterized in that: In the ZIF-8 material doped with copper ions, the doping molar amount of copper is 5-15% of the molar amount of zinc ions.
3. The core-shell-satellite SERS composite substrate with a copper-doped MOF shell layer according to claim 1, characterized in that: In the core, the molar ratio of gold in the gold nanoparticles to silver in the silver layer is 25:16.7; the molar ratio of gold in the gold nanoparticles forming the core to gold in the gold nanospheres forming the satellites is 16:
1.
4. The core-shell-satellite SERS composite substrate with a copper-doped MOF shell layer according to claim 1, characterized in that: The surfaces of the gold and silver nanoparticles are also modified with Raman probe molecules.
5. The core-shell-satellite SERS composite substrate with a copper-doped MOF shell layer according to claim 4, characterized in that: The Raman probe molecule is 4-aminothiophenol.
6. A method for preparing a core-shell-satellite SERS composite substrate having a copper-doped MOF shell layer as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: S1, preparing gold nanoparticles, and in situ coating the gold nanoparticles with a silver layer to obtain gold-silver nanoparticles; S2, using Raman probe molecules to modify gold and silver nanoparticles to obtain modified gold and silver nanoparticles; S3, modifying MOF materials doped with copper ions on the gold and silver nanoparticles modified by S2; S4. Growing gold nanospheres on the surface of the material obtained in S3 to obtain the core-shell-satellite SERS composite substrate with a copper-doped MOF shell layer.
7. The method for preparing a core-shell-satellite SERS composite substrate having a copper-doped MOF shell layer according to claim 6, characterized in that: In S1, a gold nanoparticle solution is prepared by heating and stirring an aqueous solution of chloroauric acid and an aqueous solution of sodium citrate as raw materials; an aqueous solution of silver nitrate is added to the gold nanoparticle solution under stirring, and then an aqueous solution of ascorbic acid is added, and gold-silver nanoparticles are obtained after stirring; in S2, the following steps are specifically included: the gold-silver nanoparticles are dispersed in an aqueous solution of polyvinyl pyrrolidone, mixed with an aqueous solution of Raman probe molecules after stirring, and allowed to stand after dispersion to obtain modified gold-silver nanoparticles; in S3, the following steps are specifically included: the modified gold-silver nanoparticles are dispersed in methanol, a methanol solution containing zinc nitrate and copper nitrate is added under ice-water bath conditions, a 2-methylimidazole methanol solution is added after stirring, and allowed to stand after stirring; in S4, the following steps are specifically included: the product obtained in S3 is dispersed in water, added to the stirred aqueous solution of chloroauric acid, a sodium borohydride aqueous solution is added, and stirred to obtain the core-shell-satellite SERS composite substrate with a copper-doped MOF shell layer.
8. The method for preparing a core-shell-satellite SERS composite substrate having a copper-doped MOF shell layer according to claim 7, characterized in that: In S1, the molar ratio of chloroauric acid and silver nitrate is 25:16.7; the molar ratio of chloroauric acid used in S1 to the Raman probe molecule used in S2 is 1:8; the molar ratio of chloroauric acid used in S1 to zinc nitrate and 2-methylimidazole used in S3 is 0.32:1:3; the molar ratio of chloroauric acid used in S1 to chloroauric acid used in S4 is 16:
1.
9. The method for preparing a core-shell-satellite SERS composite substrate having a copper-doped MOF shell layer according to claim 7, characterized in that: In S1, the heating and stirring temperature is 100°C and the time is 30 minutes.
10. The method for preparing a core-shell-satellite SERS composite substrate having a copper-doped MOF shell layer according to any one of claims 7 to 9, characterized in that: The amount ratio of chloroauric acid used in S1 to polyvinyl pyrrolidone used in S2 is 1 mmol:50 g; the molar ratio of chloroauric acid used in S1 to sodium borohydride used in S4 is 1:0.555.